Keberhasilan Implementasi Forest And Climate Change Programme (Forclime) oleh Indonesia – Jerman di Kalimantan - Setiawan, Angga Kurnia; Rudiany, Novita Putri (Global and Policy Journal of International Relations, 2020)
This research has questions that contained about the analysis of the success causes of the implementation of Forest and Climate Change Program (FORCLIME) by Indonesia - German in Kalimantan in the period 2010 - 2019. The answers to these research questions are then assembled into a discussion that is divided into three stages, namely the emergence of norms (norm emergence), the spread of norms (norm cascades), and the stage of internalization of norms (internalization). This proclamation was adjusted to the blade corridor of the International Norms Diffusion analysis developed by Martha Finnemore and Kathryn Sikkink in 1998. The results showed that the factor behind FORCLIME's success was due to the conformity of international norms with top-down domestic norms, regarding the reduction of domestic carbon emissions through conservation environment accompanied by economic development of the local community, which is based on Law No. 6 of 1994 concerning ratification of the United Nations Framework Convention on Climate Change (UNFCCC). Thus, the program established is closely related to the concepts of agroforestry, participatory conservation, and sustainable harvest, which are then introduced through socialization and demonstration mechanisms.Keywords : FORCLIME, Germany, Indonesia, International Norm DiffusionPenelitian ini memiliki pertanyaan yang memuat konten mengenai analisis penyebab keberhasilan Implementasi Forest and Climate Change Programme (FORCLIME) oleh Indonesia – Jerman di Kalimantan pada periode 2010 – 2019. Jawaban atas pertanyaan penelitian tersebut kemudian dirangkai menjadi sebuah pembahasan yang dibagi ke dalam tiga tahap, yaitu kemunculan norma (norm emergence), penyebaran norma (norm cascade), dan tahap internalisasi norma (internalization). Pembabakan tersebut disesuaikan dengan koridor pisau analisis Difusi Norma Internasional yang dikembangkan oleh Martha Finnemore dan Kathryn Sikkink tahun 1998. Hasilnya menunjukkan bahwa faktor dibalik keberhasilan FORCLIME itu dikarenakan adanya kesesuaian norma internasional dengan norma dalam negeri secara top-down, mengenai pengurangan emisi karbon domestik melalui pelestarian lingkungan dengan disertai pembangunan ekonomi masyarakat setempat, yang berdasar pada Undang-Undang No. 6 Tahun 1994 tentang pengesahan United Nations Framework Convention on Climate Change (UNFCCC). Sehingga, program yang dibentuk berkaitan erat dengan konsep agroforestri, konservasi partisipatif, dan panen lestari, yang selanjutnya dikenalkan melalui mekanisme sosialisasi dan demonstrasi.Kata Kunci : Difusi Norma Internasional, FORCLIME, Indonesia, Jerman DOI : https://doi.org/10.33005/jgp.v8i01.2168